Проблема личности в диалоге автора и героя «Записок из подполья» Ф.М. Достоевского - СМИРНОВ, АЛЕКСАНДР СЕМЕНОВИЧ (SlavVaria, 2021)
The problem of personality in the dialogue of the author and the hero of “Notes from the Underground” by F.M. Dostoevsky. The problem of personality in “Notes from the Underground” is considered in the article in two interrelated aspects. The first is an analysis of the anthropological views of Dostoevsky’s hero, radical for the time of the creation of the story, but positively presented in the existentialism of the twentieth century (Sartre, Camus, Frankl). The second is an analysis of the forms of expression of the author’s position, which paradoxically combines distance from the hero's ideology and attention to his point of view. Dialogism and the internal contradictoriness of the author’s position are considered as a factor that determines the structure of authorship, the organization of the narrative, the functioning of temporal images (“forty years”), the peculiarities of the plot-compositional structure of “Notes from the Underground”.